Pesticides Curbing Soil Fertility: Effect of Complexation of Free Metal Ions - Kaur, Sukhmanpreet; Kumar, Vijay; Chawla, Mohit; Cavallo, Luigi; Poater, Albert; Upadhyay, Niraj (Frontiers in Chemistry, 2017)
Researchers have suggested that the reason behind infertility is pernicious effect of broad spectrum pesticides on non target, beneficial microorganism of soil. Here, studying the chelating effect of selective organophosphate and carbamate pesticides with essential metal ions, at all possible combinations of three different pH (4±0.05, 7±0.05 and 9±0.05) and three different temperatures (15±0.5°C, 30±0.5°C and 45±0.5°C), shows very fast rate of reaction which further increases with increase of pH and temperature. Carbonyl oxygen of carbamate and phosphate oxygen of organophosphate were found to be common ligating sites among all the complexes. Formed metal complexes were found to be highly stable and water insoluble on interaction with essential metal ions in solvent medium as well as over silica. Density functional theory (DFT) calculations not only reinforced the experimental observations, but, after a wide computational conformational analysis, unraveled the nature of the high stable undesired species that consist of pesticides complexed by metal ions from the soil. All in all, apart from the direct toxicity of pesticides, the indirect effect by means of complexation of free metal ions impoverishes the soil.